STXMPy: a new software package for automated region of interest selection and statistical analysis of XANES data - Haraszti, Tamás; Grunze, Michael; Anderson, Michael G. (Chemistry central journal, 2010)
Soft X-ray spectromicroscopy based absorption near-edge structure analysis, is a spectroscopic technique useful for investigating sample composition at a nanoscale of resolution. While the technique holds great promise for analysis of biological samples, current methodologies are challenged by a lack of automatic analysis software e. g. for selection of regions of interest and statistical comparisons of sample variability.